The South African Response to COVID-19 The Early Years - Fourie, Pieter; Lamb, Guy (Routledge Studies in Health in Africa, 2023)
This book analyses the first two years of South Africa's response to the COVID-19 epidemic, from its emergence in early 2020. Drawing on the perspectives of a range of public health experts, economists and other social scientists and development practitioners, the book argues that understanding this early response will be essential to moderate and improve future policy thinking around health governance and epidemic readiness. The book provides systemic analysis of not only the epidemiological progression of COVID-19 in South Africa, but also the socio-political factors that will be key in determining the future of the country as a whole: including health system challenges, socio-economic disparities and inequalities, and variable (often contradictory and tardy) policy responses. Overall, the book exposes Manichean thinking and the spurious policy dichotomies that pitch public health against human rights, economic recovery against viral vector control, and science against ideology, with lessons not just for South Africa, but also for elsewhere on the African continent, and beyond. This book will be perfect for researchers and practitioners across Public Health, Health Policy, and Global Health, as well as those with an interest in South African politics and development more generally.